Spider Grass Cutter - Zahar, Mohd Muzaffar; Kamil, Amirul Ashraf; Mohd Zamurina, Nurul Nabila; Mohd Razali@Kamaruddin, Nur Aida Nabilah (Penerbit UTHM, 2020)
The regular lawn mower requires manual handling to run and it also uses fuel as the power source in the cutter component. There are a few disadvantages of the regular grass cutter. First, the operation cost of a regular grass cutter increases as the fuel price increases. Second, it is heavy and thus requires a lot of energy to push around. Third, it produces a lot of noise that will disturb the neighbours and surrounding areas. Considering the facts, a project to redesign the handling of a regular grass cutter is proposed by focus on developing the light, easy to carry and easy to store machine system. This proposed system will help the housewives especially to use the mower itself and with little assistance.